Effect of Dysprosium-Compounds Treatment on Coercivity of Nd-Fe-B Sintered Magnets - Dhakal, Dhani Ram; Namkung, Seok; Lee, Min-Woo; Jang, Tae-Suk (Current Nanoscience, 2014)
In order to find an effective method to increase the coercivity of Nd-Fe-B magnets using less Dy quantity, an ordinaryprocessed Nd-Fe-B sintered magnet was treated with dysprosium-compound suspension in this work. After the magnets were prepared by a normal sintering process, they were cut into the size of 10 x10 x5 mm3 pieces and then dipped in 20 % DyF3 suspension and 20 % DyHx suspension, for one minute, so that the magnets were coated with the dysprosium compounds. These coated magnets were further subjected to heat treatment. As a consequence, coercivity of the coated magnets was increased over 255 kAm-1 for Dy-contained one and 243 kAm-1 for Dy-free one without noticeable reduction in the remanence and the energy product values. This improvement of the coercivity was due to Dy diffusion along grain boundaries from the surface of the coated magnets, thereafter, a partial replacement of Nd in Nd2Fe14B main grain by Dy had taken place near the grain boundaries, resulting in the increase of anisotropy field in that area.
Keywords: Coating